Development of Digital Book Learning Media on The Subject Geography Environmental Material Geosphere: Atmospheric Dynamics at Sma Negeri 1 Gorontalo Utara - Dahlan, Firna Ananta R. (Universitas Bengkulu, 2024)
Research into the development of digital book learning media is essential because it can increase learning effectiveness, accommodate diverse learning styles, facilitate understanding of concepts, encourage student involvement, and facilitate learning evaluation. Developing learning media in digital books aims to produce products and analyze the feasibility of developing digital book learning media for students. This Research is a type of development research using the ADDIE development model, which consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The results obtained from the Research show that the assessment obtained from material experts was 93.33%, which was included in the Very Appropriate criteria, the media expert's assessment was 85%, which was included in the Very Appropriate criteria, the assessment from subject teachers reached 94.07%, which was including the Very Eligible criteria, and for student assessment on the limited test, 84.7% was obtained including the Very Eligible criteria. The general test results obtained were 88.6% with very feasible criteria. Based on the validation and trials results, digital book media is suitable to be a digital book media in geography subjects with atmospheric dynamics material.